Basic Concepts of PAI Learning System Planning - Suriyanti, Suriyanti; Karolina, Asri; Idris, Muhammad (CV Media Inti Teknologi, 2024)
This study aims to identify the fundamental ideas behind the planning of the Pendidikan Agama Islam (PAI) learning system. This study employed a liberal research methodology, drawing instances from earlier classes and basing it on written tests. This study is qualitative. Data collection comes from logical diary articles, news from local governments, and research results from theories and books. The result of this PAI Learning system planning research is to bring innovations to the world of education so that teachers know that learning system planning integrates teachers into the performance of their educators' duties to meet student learning needs. However, PAI learning system planning is not done independently but is carried out through activities involving individuals. Thus, it can be said that the learning system is influenced by a number of elements and circumstances.